Generic Structure Potential of Christian Apologetics - Inya, Onwu (Linguistik Online, 2012)
Religious texts have been examined by scholars from different theoretical standpoints. However, a close survey of the literature reveals that little attention has been paid to Christian apologetics from a linguistic perspective. Also, an examination of studies along the lines of Generic Structure Potential (henceforth GSP) shows that the genre status of Christian apologetics has not been indicated. This gap provides the motivation for this paper, which investigates the GSP of Christian apologetics. Twenty texts written by various key contemporary apologetic writers were purposively selected for the study. The following generic structure potential catalogue was generated: The paper reveals that the elements of the GSP concertedly work to advance, argue for or defend the Christian belief system. The paper also suggests that the model could be applied to other forms of apologetic instances.